2015
DOI: 10.1139/cjm-2015-0073
|View full text |Cite
|
Sign up to set email alerts
|

Insights into thermoadaptation and the evolution of mesophily from the bacterial phylum Thermotogae

Abstract: Thermophiles are extremophiles that grow optimally at temperatures >45°C. To survive and maintain function of their biological molecules, they have a suite of characteristics not found in organisms that grow at moderate temperature (mesophiles). At the cellular level, thermophiles have mechanisms for maintaining their membranes, nucleic acids, and other cellular structures. At the protein level, each of their proteins remains stable and retains activity at temperatures that would denature their mesophilic homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 150 publications
2
69
0
Order By: Relevance
“…However, it is unclear how growth temperature affects other aspects of genome evolution including levels of homologous recombination. Hyperthermophilic Thermotoga display extremely high levels of homologous recombination, which could be a side effect of the need for DNA repair at high temperatures (Nesbø et al, 2015). Nesbø et al (2015) also found high levels of geneflow among all Thermotoga spp.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…However, it is unclear how growth temperature affects other aspects of genome evolution including levels of homologous recombination. Hyperthermophilic Thermotoga display extremely high levels of homologous recombination, which could be a side effect of the need for DNA repair at high temperatures (Nesbø et al, 2015). Nesbø et al (2015) also found high levels of geneflow among all Thermotoga spp.…”
Section: Introductionmentioning
confidence: 98%
“…Hyperthermophilic Thermotoga display extremely high levels of homologous recombination, which could be a side effect of the need for DNA repair at high temperatures (Nesbø et al, 2015). Nesbø et al (2015) also found high levels of geneflow among all Thermotoga spp. genomes investigated, and that populations from similar environments have exchanged more genes than geographically close populations from different environments.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations